Straits of Malacca and Singapore : ensuring safe navigation - Mohd Hazmi Mohd Rusli (2012)
The Straits of Malacca and Singapore are two of the world’s most congested straits used for international shipping. There are existing hazards impeding safe navigation through the Straits. What would be the impact of a proposed bridge linking Sumatra and Malaysia?